Four ways of Listening to an iPhone: From Sound and Network Listening to Biometric Data and Geolocative Tracking - Crawford, Kate (Studying Mobile Media: Cultural Technologies, Mobile Communication, and the iPhone, 2012)
The iPhone represents an important moment in both the short history of mobile media and the long history of cultural technologies. Like the Walkman of the 1980s, it marks a juncture in which notions about identity, individualism, lifestyle and sociality require rearticulation. this book explores not only the iPhone’s particular characteristics, uses and "affects," but also how the "iPhone moment" functions as a barometer for broader patterns of change. In the iPhone moment, this study considers the convergent trajectories in the evolution of digital and mobile culture, and their implications for future scholarship. Through the lens of the iPhone—as a symbol, culture and a set of material practices around contemporary convergent mobile media—the essays collected here explore the most productive theoretical and methodological approaches for grasping media practice, consumer culture and networked communication in the twenty-first century.